Paciente de 22 años de edad que presenta insuficiencia renal crónico. - Márquez Villacís, Jeniffer Estefanía (2020)
In the following study of the clinical case it is based on a 22-year-old female patient, who suffers from chronic renal insufficiency, hemodialysis is performed, with a family history of Diabetes mellitus and Arterial Hypertension. As a result of the physical examination, located in time and space. With a now-painful soft abdomen, shiny hair. Not edema, the anthropometric assessment reveals the body mass index of 18.1kg/m2 according to the cut-off points of the world health organization (WHO, 1995), it presents a low weigh nutritional with energy deficit grade 1 and moderate cardiovascular risk. The comprehensive nutritional diagnosis is made using anthropometric parameters. The biochemical values show that urea 51ml/dl and creatinine 2.28ml/dl are elevated: As for dietary elevation or food history, an inadequate intake of macro- micronutrients is evident. Our goal is to improve the nutritional status of the patient though a correct nutritional intervention, with a diet plan of 1470 kcal/day, hyposodic diet with 1.5g/day of sodium, 50.4/day hyperprotein protein diet. Fractionated into 5 meals a day according to your caloric requirement and thus provide improvement in your patient’s health and eating habits avoiding future complications.